Toll-like Receptors and Periodontitis: Current Insights into Immune Dynamics and Translational Therapeutics - Liew, Fong Fong; Tan, Soon Hao; Sengupta, Pallav; Dutta, Sulagna (Trends in Immunotherapy, 2026)
Periodontitis is a common and persistent inflammatory disease resulting from a sophisticated relationship between oral bacteria and the body’s immune system. Toll-like receptors (TLRs) act as crucial sensors within the immune response, playing a fundamental role in the disease’s initiation and progression. This review examines periodontitis, highlighting the limited understanding of TLR activation mechanisms and the therapeutic potential of TLR inhibitors. The discussion begins with a definition of TLRs, outlining their characteristics, types, distribution, and activation mechanisms. It then details the manifestation of TLRs in periodontitis, including alterations during inflammation and their correlation with disease severity. TLR activity is influenced not only by microbial stimuli but also by epigenetic factors and miRNAs, which mediate gene expression changes linked to inflammation. Various miRNAs have been shown to regulate TLR signaling pathways, thereby modulating the inflammatory response in periodontal tissues. Additionally, epigenetic modifications further complicate the landscape of immune regulation in periodontitis, affecting TLR expression and function. This interplay between TLRs, miRNAs, and epigenetic changes underscores the systemic implications of periodontal disease, contributing to broader health issues. Consequently, the review explores innovative strategies to modulate TLR signaling and discusses future challenges in TLR research in relation to periodontitis treatment. In summary, a more profound understanding of TLR-driven immune responses, along with the regulatory roles of miRNAs and epigenetic factors, is essential for developing targeted therapies and advancing treatment options for periodontitis.